Thermodynamic stability and control of oxygen reactivity at functional oxide interfaces: EuO on ITO. Issue 9 (8th February 2016) - Gerber, Timm; Lömker, Patrick; Zijlstra, Bernardus; Besson, Claire; Mueller, David N.; Zander, Willi; Schubert, Jürgen; Gorgoi, Mihaela; Müller, Martina
Abstract : How thermodynamic properties affect the growth, interface chemistry and magnetic functionality of the ferromagnetic insulator EuO on transparent and conductive ITO is studied by employing HAXPES as a powerful non-destructive and element-sensitive probing technique. Abstract : As a prototypical all-oxide heterostructure, the ferromagnetic insulator europium monoxide (EuO) is synthesized on transparent and conductive indium tin oxide (ITO) virtual substrates. Non-destructive hard X-ray photoelectron spectroscopy is employed to depth profile the chemical composition of the magnetic layer and the buried oxide–oxide interface. We find that thermally activated oxygen diffusion from ITO affects the EuO growth process. We present how to control the oxygen reactivity at the interface and discuss its origin in a thermodynamic analysis. Our complementary methodical strategy allows for a significant improvement of the EuO chemical quality with sizeable magnetic properties. Generally, our approach derives guidelines for the proper choice of oxide substrates and buffer layer materials for functional all-oxide heterostructures.